Morphology of pupae of five species of the genus Bembecia—group ichneumoniformis (Lepidoptera: Sesiidae) - Bąkowski, Marek; Fajfer, Daniel (Zootaxa, 2019)
This work presents the first descriptions of the pupal morphology of five species of western Palaearctic clearwing moths Bembecia abromeiti Kallies & Riefenstahl, 2000, B. handiensis (Rämisch, 1997), B. lomatiaeformis (Lederer, 1853), B. psoraleae Bartsch & Bettag, 1997, and B. vulcanica (Pinker, 1969) in the genus Bembecia—subgroup ichneumoniformis. The main morphological features are described and illustrated with photographs and line drawings. Diagnostic characters, as well a key for the determination of pupae of the studied species and related taxa, Bembecia ichneumoniformis (Denis & Schiffermüler, 1775) and B. albanensis (Rebel, 1918) are presented.